Novel Use of Dual Guiding Catheters Technique to Prevent Distal Embolization and Slow Flow during PCI of Coronary Stent Thrombosis - Trehan, Vijay Kumar; Jain, Gagan; Gupta, Puneet (International Journal of Angiology, 2021)
Despite having an incidence of 0.5 to 2%, stent thrombosis has an in-hospital mortality of 15% and myocardial infarction (MI) incidence of 67%. Even with the usage of thrombus aspiration devices and microvasculature vasodilators such as nitroprusside, verapamil, adenosine, and Gp2b/3a inhibitors, the angiographic result of percutaneous coronary intervention of coronary stent thrombosis remains frequently suboptimal due to distal embolization and subsequent slow flow. We describe a novel use of dual guide catheter technique, where one guide acts as conduit for thrombus aspiration catheter and the other for distal placement of balloon trap to prevent distal embolization while managing a case of coronary stent thrombosis to improve the angiographic outcome in this scenario.
Keywords: stent; PCI; myocardial infarction; coronary stent; coronary artery; guiding catheter